Effect of density in single and double row arrangements on the yield of dryland beans in Chihuahua, Mexico - Jiménez Galindo, José Cruz; Acosta Gallegos, Jorge Alberto (Revista Mexicana de Ciencias Agrícolas, 2018)
We describe studies on the use of high densities of dryland beans in the state of Chihuahua. Most producers of irrigated beans planted at a density below INIFAP recommendations. The objectives of the studies reported here were: a) to make a random sampling in commercial plots of dryland beans in Chihuahua to determine the population of plants in use; and b) to evaluate the performance of the dryland Pinto Saltillo variety at different densities, locations and years. The sampling of the density of dryland bean plots was made in 2009. The experiments for determining the use of high or optimal densities were performed in 2010 in Bachiniva, Bachiniva, and in 2011 in Carbajal de Abajo, Cusihuiriachi and Felipe Angeles, Namiquipa. Fertilization and management varied according to the producer. The densities used varied from 2 to 16 plants per meter (plants m-1). The average density recommended for dryland beans in the three localities was 8 to 16 plants m-1 (100 000 to 200 000 plants per hectare at harvest), depending on the soil type, crop management and amount and distribution of rainfall in the year.
Keywords: Phaseolus vulgaris L.; optimal density; dryland beans